Membangun Karakter Tangguh dan Berintegritas melalui Edukasi Film Sang Penantang di Desa Pakang, Kecamatan Andong, Kabupaten Boyolali - Muin Abdullah; Achmad Rasyid Ridha (LPMP Imperium, 2025)
Character building is essential to personal and societal development, particularly for the younger generation, which will shape the future. However, the rapid advancement of technology and exposure to negative influences pose challenges in fostering individuals with strong integrity and resilience. This Community Service Program (PKM) utilizes the educational film Sang Penantang as a medium to instill moral values in the youth of Pakang Village, Andong District, Boyolali Regency. The program integrates film screenings, interactive discussions, and self-reflection activities to enhance participants' understanding of perseverance, honesty, and determination. This activity was conducted on February 16, 2025. The program implementation involved several stages: socialization, film screenings, group discussions, and individual reflections. The results indicate a significant improvement in the participants' comprehension and application of character values in daily life. Many expressed increased awareness of the importance of integrity, responsibility, and persistence. The success of this initiative highlights the potential of educational films as an effective tool for character education. Future programs may expand through collaborations with academic institutions and youth organizations to ensure a broader and more sustainable impact.